Educational Game Learning Japanese Language - Oh Daniel Kurniawan; Hendra Prasetya; Bernadinus Harnadi (Journal of Business and Technology, 2021)
Language and culture is an applied been possessed by every man since born. Language is a in the form of communication with  each  other.  In daily life, communicate with the family, friend, even work also need good ability. Therefore a  use of language that well and properly should be owned individuals[1]. Nihon-Goo! Is a Game made from computer for the purpose as a medium and facilitate the process increase knowledge and understanding basic vocabulary and culture in japan. After 5 times playing of one each day, game testing was conducted to 40 people and fill the questionnaire. Post-test data result shows that the game makes the player having  difficulty answering  the questions, but still want to play it again and again. So even though they failed to try it, they still tried again and again.